Writing Workshop: The Author Character Training Strategy - Ahmad Ridhani (STKIP Singkawang, 2018)
The activity of writing is indispensable in everyday life, both in the life of society and in academic life. The life of the society marked the existence of communication through writing or writing manual recording via social media. The activities of the academic life were marked in writing the existence of communication in various academic activities. Write various documents required as evidence of the existence of an activity that can be accounted for. writing workshop project (WWP) aims to train skills and writing skills, and develop the character of the author. Abilities and writing skills include: (1) the ability to use the techniques and are assigned grammatical the writing; (2) choice of words; and (3) the ability of arguing. The construction and development of the author's character is closely related to (1) the ability of thinking ability, (2) reasoning, (3) academic ability, social abilities (4), (5) emotional ability, and (6) the ability of aesthetics..